Scion-rootstock combinations for orange trees in the state of Amazonas - Milena Dantas Ribeiro; Gustavo Brazão Buzaglo; Daniely Cunha da Silva; Laiane Sherly Gomes Torres; Ana Francisca Tibúrcia Amorim Ferreira e Ferreira; Débora Clivati Faria Pereira; Cláudio Luiz Leone Azevedo; José Ferreira da Silva (Ciência Rural)
ABSTRACT: In the state of Amazonas, the ‘Pêra’ orange scion is traditionally cultivated on ‘Rangpur’ lime tree. The restricted use of a single scion-rootstock combination has left local orchards vulnerable to adverse conditions and incidence of pests and diseases, which may negatively interfere with both productivity and fruit quality and the citrus activity sustainability in the state. The expansion of the number of scion-rootstock combinations becomes a viable alternative to overcome such problems. To meet this demand from citrus growers, 30 combinations with 10 scions and 3 rootstocks were evaluated in the sixth and seventh year after planting seedlings in the field in the municipality of Rio Preto da Eva, AM. In this experiment, productivity, juice yield, soluble solids, pH, titratable acidity, ratio and technological index were evaluated. ‘Pineapple’ scion with ‘Sunki Tropical’ and ‘BRS Bravo’ rootstocks can be productive alternatives in relation to traditional ‘Pêra’ orange scion under ‘Rangpur’ lime combination in the state of Amazonas. ‘Lima’ orange with ‘Sunki Tropical’ mandarin, ‘Rangpur lime SC’ and ‘BRS Bravo’ lime rootstocks can be alternatives for the fresh market in the state. Combinations that showed good fruit quality are ‘Pêra’, ‘Salustiana’, ‘Valência Tuxpan’ and ‘Westin’ scions with ‘BRS Bravo’ rootstock, and ‘Pêra D6’ scion with ‘Rangpur lime SC’ lemon rootstock. These combinations are alternatives for the diversification of orchards in the state of Amazonas.